Increased Th17 cells in flow cytometer-sorted CD45RO-positive memory CD4 T cells from patients with systemic lupus erythematosus. Issue 1 (11th December 2014) - Liu, Ming-Fei; Wang, Chrong-Reen
Abstract : Objectives: Th17/IL-17 dysregulation is involved in human autoimmunity, and recent evidence suggests the character of long-lived differentiated memory cells in Th17. By directly measuring the peripheral blood mononuclear cells (PBMC), elevated circulating frequencies of Th17 cells have been reported in systemic lupus erythematosus (SLE) with inconsistent results regarding the correlation with disease activities. In this study, the association between circulating Th17 frequencies and disease activities or laboratory parameters was examined in flow cytometer-sorted CD45RO-positive memory CD4 T cells from SLE. Methods: PBMC samples were obtained from 48 female lupus patients and another 48 age- and sex-matched healthy individuals. We examined frequencies of Th17 cells by sorting the purified CD4 T cells bearing the CD45RO marker, followed by intracellular IL-17A staining after in vitro activation. Frequencies of Th1 and TFoxp3 cells were also measured by intracellular IFN-γ and Foxp3 staining, respectively. The SLE disease activity index (SLEDAI) and other laboratory parameters were further correlated with frequencies of different T cell subsets. Results: In SLE, increased frequencies of Th17 cells were found with a positive correlation in SLEDAI. Higher frequencies of Th17 cells were found in lupus nephritis. There was a positive correlation between frequencies of Th17 cells and daily proteinuria amount. Conclusions: By examining the sorted CD45RO-positive memory CD4 T cells, we confirm the dysregulation of Th17/IL-17 in SLE, implicating the potential to treat lupus patients with selective IL-17/IL-17R blockades.